Blueprint of Bellissima Hijab Prima Enterprise / Rusni Azreen Razmi - Razmi, Rusni Azreen (2020)
Bellissima Hijab Prima Enterprise which is known as BH Prima Enterprise is a company that produces high quality products of headscarves. BH Prima Enterprise is a manufacturing firm that was formed under a partnership on 4th January 2020 owned by five partners. The location of our office and factory is located at 18 UDA Business Center, Jln Padi Emas 1/3, Bandar Baru Uda, 81200 Johor Bahru, Johor. Meanwhile our physical store is at 24 UDA Business Center, Jalan Padi Emas 1/4, Bandar Baru Uda, 81200 Johor Bahru, Johor. It is indeed the most strategic location that can attract many customers to achieve the company main target market goal